RECURRENT RESPIRATORY PAPILLOMATOSIS - Yu.L. Soldatskiy (Вопросы современной педиатрии, 2007)
Contemporary views on etiology, pathogenesis, clinical course, diagnotics, surgical and preventive recurrence treatment of respiratory papillomatosis in childen are analyzed in this article.Key words: recurrent respiratory papillomatosis, childhood, larynx.